The Genetic Relationship between Paroxysmal Movement Disorders and Epilepsy - Hyunji Ahn; Tae-Sung Ko (Korean Child Neurology Society, 2020)
Seizures and movement disorders both involve abnormal movements and are often difficult to distinguish due to their overlapping phenomenology and possible etiological commonalities. Paroxysmal movement disorders, which include three paroxysmal dyskinesia syndromes (paroxysmal kinesigenic dyskinesia, paroxysmal non-kinesigenic dyskinesia, paroxysmal exercise-induced dyskinesia), hemiplegic migraine, and episodic ataxia, are important examples of conditions where movement disorders and seizures overlap. Recently, many articles describing genes associated with paroxysmal movement disorders and epilepsy have been published, providing much information about their molecular pathology. In this review, we summarize the main genetic disorders that results in co-occurrence of epilepsy and paroxysmal movement disorders, with a presentation of their genetic characteristics, suspected pathogenic mechanisms, and detailed descriptions of paroxysmal movement disorders and seizure types.